Id Reaction: An Overlooked Reaction of a Common Problem - Pathak, Deptara (Medical Journal of Shree Birendra Hospital, 2010)
A 15 year old boy presented with sudden onset of pompholyx like eruption on acral areas involving bilateral hands and feet for 2 weeks. Clinical examination showed multiple vesicubullous eruptions on dorsum of bilateral foot, dorsum of hands. There was a focus of intertriginous dermatitis involving right lateral toe cleft with maceration and fissuring. A scraping from the lesion demonstrated fungal hyphae with 10% KOH preparation but not from the vesicular eruption. A diagnosis of Id reaction due to Tinea Pedis was made. Patient was started on topical and oral antifungal along with antihistamines and he responded well with the treatment. Key words: Id reaction; T.Pedis (Tinea pedis) DOI: 10.3126/mjsbh.v9i1.3485 Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 17-18